2006
DOI: 10.1182/blood-2005-05-1916
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of yolk sac hematopoiesis by Krüppel-like factor 6

Abstract: Krü ppel-like factor 6 (KLF6) is a member of a growing family of transcription factors that share a common 3 C 2 H 2 zinc finger DNA binding domain and have broad activity in regulating proliferation and development. We have previously established that Klf6 is expressed in neuronal tissue, hindgut, heart, lung, kidney, and limb buds during midgestation. To explore the potential role of Klf6 in mouse development, we analyzed Klf6 ؊/؊ mice and found that the homozygous mutation is embryonic lethal by embryonic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
126
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 67 publications
8
126
0
Order By: Relevance
“…Moreover, KLF6 is expressed from very early stages during human placental development, colocalizing with PSG transcripts and proteins within the same tissue structures and cell types, suggesting a relevant role of this factor for the transcriptional regulation of PSG genes in vivo (14). Additionally, the klf62/2 mice phenotype is characterized by developmental defects including impaired placental development and poorly defined liver contributing to early lethality along with failures in the yolk sac vascularization (15). Besides the enriched KLF6 expression in placenta, its transcript is also detected in all mammalian tissues, although at lower levels; whereas, marginal expression was detected at the embryo proper during mice embryogenesis (12).…”
Section: Discovery Of Klf6: a Key Regulator Of Cell Homeostasis And Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, KLF6 is expressed from very early stages during human placental development, colocalizing with PSG transcripts and proteins within the same tissue structures and cell types, suggesting a relevant role of this factor for the transcriptional regulation of PSG genes in vivo (14). Additionally, the klf62/2 mice phenotype is characterized by developmental defects including impaired placental development and poorly defined liver contributing to early lethality along with failures in the yolk sac vascularization (15). Besides the enriched KLF6 expression in placenta, its transcript is also detected in all mammalian tissues, although at lower levels; whereas, marginal expression was detected at the embryo proper during mice embryogenesis (12).…”
Section: Discovery Of Klf6: a Key Regulator Of Cell Homeostasis And Dmentioning
confidence: 99%
“…Nevertheless, a number of other studies established that genetic alterations of KLF6 were infrequently observed in distinct types of human cancers or even the klf6 gene expression was enhanced in some tumors (29). Moreover, target disruption of the klf6 gene severely impaired ES cell proliferation (15). In addition, p21…”
Section: Discovery Of Klf6: a Key Regulator Of Cell Homeostasis And Dmentioning
confidence: 99%
“…In light of the mounting number of studies reporting KLF6 involvement in HCC through LOH and/or mutation, and to further establish a direct relationship between KLF6 and p21 in vivo, we characterized the livers of KLF6 heterozygous (Het) mice that had been generated by homologous recombination and targeting of KLF6 exon 2, as described previously (Matsumoto et al, 2006). Two independent lines of mice, AH2 and CH2, were generated and Het AH2 mice were examined.…”
mentioning
confidence: 99%
“…All Klf knockouts generated thus far are embryonic lethal (20 -22), including the Klf6 knock-out mice (23). Because prostate development begins in late gestation and continues postnatally, we overcame embryonic lethality to study the role of Klf6 in prostate development and tumorigenesis by generating a prostate-specific deletion of the Klf6 gene using a Cre-lox recombination approach.…”
mentioning
confidence: 99%